DIKSI, GAYA BAHASA, DAN PERMAINAN BUNYI PADA LIRIK LAGU-LAGU MELAYU - Isyatur Radhiyah (Universitas Lambung Mangkurat, 2018)
AbstractDiction, Language Style and Sound Games on Lyrics of Melayu Songs. This study aims to determinethe aesthetic value in the lyrics of melayu songs sung by Ahmad Jais. This research is directed towardsthe lyrics of melayu songs which are more prominent in terms of diction, language style and soundgames that are used specifically to create certain effects, especially aesthetic effects.This research is adescriptive qualitative research using content analysis method. The researchers took as many as 10 lyricsof melayu songs sung by Ahmad Jais.The results showed that the dictions or choice of words in the lyricsof melayu songs sung by Ahmad Jais use both connotative and denotative meanings. There are 160diction which meanings are divided into two; 80 data with connotative meanings and 80 data withdenotative meanings. This choice of words helps the author to convey the message he wants to deliver andto add the beauty of the songs’ lyrics. The most widely used language style based on the choice of wordsis the unofficial language style found as many as 8 data. The most widely used language style accordingto the tone contained in the discourse is the powerful noble language as many as 5 data. The most widelyused in language style according to mostly used sentence structure is the climax, as many as 7 data.The most widely used language style according to the direct or indirect meaning is the style of rhetoricallanguage, as many as 10 data. From the document analysis of the lyrics of melayu songs from soundelements, it can be seen that there are 174 data from taxation elements consisting of 34 alliteration data,134 assonance data and 6 data of the combination of alliteration and assonance. From the element ofrhythm, there are 10 kinds of euphony. From the elements of the tone and the atmosphere, which are 2data of sad atmosphere, 2 data of joyful atmosphere, and 6 data of powerless atmosphere.Key words: diction, language style and sound gamesAbstrakDiksi, Gaya Bahasa dan Permainan Bunyi pada Lirik Lagu-Lagu Melayu. Penelitian ini bertujuanuntuk mengetahui nilai keindahan yang terkandung dalam lirik lagu-lagu melayu yang dibawakanoleh Ahmad Jais. Penelitian ini diarahkan terhadap lirik dalam lagu-lagu melayu yang lebih menonjoldari segi diksi, gaya bahasa dan permainan bunyi yang digunakan secara khusus untuk menimbulkanefek tertentu, khususnya efek estetis.Penelitian ini merupakan penelitian deskriptif kualitatif denganmenggunakan metode analisis isi. Peneliti mengambil data sebanyak 10 lirik lagu-lagu melayu yangdibawakan oleh Ahmad Jais. Hasil penelitian menunjukkan bahwa diksi atau pilihan kata dalam liriklagu-lagu melayu yang dibawakan oleh Ahmad Jais menggunakan makna konotatif dan juga makna205denotatif. Ada 160 data terdapat diksi, yang bermakna konotatif 80 data dan diksi yang bermaknadenotatif 80 data. Pilihan kata ini membantu penulis untuk menyampaikan pesan yang ingindisampaikannya dan menambah keindahan lirik lagunya. Gaya bahasa menurut pilihan kata yangpaling banyak digunakan adalah gaya bahasa tidak resmi sebanyak 8 data. Gaya bahasa menurut nadayang terkandung dalam wacana yang paling banyak digunakan adalah gaya bahasa mulia bertenagasebanyak 5 data. Gaya bahasa menurut struktur kalimat yang paling banyak digunakan adalah klimakssebanyak 7 data. Gaya bahasa menurut langsung tidaknya makna yang paling banyak digunakanadalah gaya bahasa retoris sebanyak 10 data. Dari analisis dokumen lirik lagu-lagu melayu dari unsurbunyi dapat diketahui ada 174 data dari unsur persajakan yang terdiri dari 34 data aliterasi dan 134data asonansi serta 6 data kombinasi aliterasi dan asonansi. Dari unsur irama ada 10 jenis efoni. Dariunsur nada dan suasana, yaitu suasana sedih ada 2 data, suasana gembira ada 2 data, dan suasana takberdaya ada 6 data.Kata-kata kunci: diksi, gaya bahasa, permainan bunyi